PENGARUH JENJANG KARIER DAN STRES KERJA TERHADAP KEPUASAN KINERJA KARYAWAN PT. BANK BPR JATIM BANK UMKM JAWA TIMUR CABANG KEDIRI - Paramita, Rima Dana; Sugiono; Purnomo, Hery (Universitas Nusantara PGRI Kediri, 2022)
The researcher analyzed the influence of career path variables and work stress variables on the performance satisfaction variable of BBPR Kediri employees. This study uses a descriptive quantitative approach, using primary data from the distribution of questionnaires. This study uses a saturated sample technique from a total of 32 respondents. The data analysis technique used multiple linear regression analysis using SPSS. The research findings found that there was an effect of career path on employee performance satisfaction, the influence of work stress on employee performance satisfaction and career path and work stress together gave a significant influence on employee performance satisfaction of BBPR Kediri